HIV and coronary arterial remodeling from the Multicenter AIDS Cohort Study (MACS). Issue 2 (August 2015) - Miller, P.Elliott; Haberlen, Sabina A.; Metkus, Thomas; Rezaeian, Panteha; Palella, Frank; Kingsley, Lawrence A.; Witt, Mallory D.; George, Richard T.; Jacobson, Lisa P.; Brown, Todd T.; Budoff, Matthew; Post, Wendy S.
Abstract: Objective: Positive remodeling (PR), a coronary artery characteristic associated with risk for myocardial infarction (MI), may be more prevalent in HIV-infected (HIV+) people. We evaluated the prevalence of PR using coronary CT angiography (CCTA) in HIV+ and HIV-uninfected (HIV−) men. Methods: Men enrolled in the Multicenter AIDS Cohort Study underwent CCTA if they were 40–70 years, had normal kidney function and no history of coronary revascularization. Multivariable logistic regression models were used to estimate the odds ratio (OR) of PR by HIV serostatus, adjusting for demographics and coronary artery disease (CAD) risk factors. Analysis of PR among atherosclerotic segments further adjusted for plaque type and stenosis. Results: The prevalence of PR was 8.4% versus 12.1% (p = 0.10) for HIV- and HIV + men, respectively. After demographic adjustment, HIV + men had twice the odds of PR [OR 2.01(95% CI 1.20–3.38)], which persisted after CAD risk factor adjustment [1.76(1.00–3.10)]. Higher systolic blood pressure, total cholesterol, diabetes medication use, older age, segment number with plaque present, mixed and non-calcified plaque, and stenosis>50%, were associated with increased odds of PR, while higher HDL cholesterol, higher nadir CD4 count, and black race were associated with lower PR odds. Among atherosclerotic segments, the association between HIV infection and PR persisted, but was not statistically significantly. Conclusion: HIV+ men have more positively remodeled arterial segments, which may be due to more coronary segments with atherosclerosis or HIV-related immunosuppression. Further studies are needed to evaluate whether PR contributes to higher rates of MI in HIV+ individuals. Highlights: HIV+ men had more coronary artery segments with positively remodeling (PR). PR is associated with a history of AIDS and inversely with nadir CD4+ T-cell count. PR is associated with age, systolic BP, elevated cholesterol, and diabetes meds. PR is more likely in coronary segments with non-calcified plaque.